Two new species of Microlia Casey (Coleoptera: Staphylinidae) with comments on obligatory pollen-feeders and the first record from South America - Bortoluzzi, Sidnei; Caron, Edilson; Silveira, Denise (Zootaxa, 2016)
Microlia Casey, 1910 is a small genus that currently includes twelve species distributed in Australasian and New World regions. Here, two new species of Microlia—M. amici sp. nov. (holotype male deposited in DZUP: Brazil, Paraná State) and M. machadoi sp. nov. (holotype male deposited in DZUP: Brazil, Rio Grande do Sul State)—are described and illustrated. M. amici sp. nov. differs from M. meticola by abdominal segments darker, mesotarsus with 5 segments, tergum VII of male without tubercles, and tergum VIII of male emarginated in posterior margin. While, M. machadoi sp. nov. differs from M. pentamera and M. tetramera by curved spine-like in the posterior margin of tergum III. Additional comments on their pollen-feeders habits that are available from morphological and natural history data, and the distribution of the genus is extended in the New World, now including the first time record for South America.